2014
DOI: 10.1186/1757-2215-7-25
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics associated with spontaneous differentiation of ovarian stem cells in vitro

Abstract: BackgroundRecent studies suggest that ovarian germ line stem cells replenish oocyte-pool in adult stage, and challenge the central doctrine of ‘fixed germ cell pool’ in mammalian reproductive biology. Two distinct populations of spherical stem cells with high nucleo-cytoplasmic ratio have been recently identified in the adult mammalian ovary surface epithelium (OSE) including nuclear OCT-4A positive very small embryonic-like (VSELs) and cytoplasmic OCT-4 expressing ovarian germ stem cells (OGSCs). Three weeks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
67
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(80 citation statements)
references
References 52 publications
(84 reference statements)
12
67
0
1
Order By: Relevance
“…Based on these results and our earlier studies, 2,17,18 we propose in mouse ovary that small nuclear OCT-4 positive cells represent VSELs, while the slightly larger cytoplasmic OCT-4 positive cells represent OGSCs. To further confirm that VSELs are present in mouse ovary, flow cytometry experiment based on SCA-1þ/LinÀ/CD45À expression unique to VSELs 24 was carried out.…”
Section: Effect Of Chemotherapy On Mouse Ovarian Follicular Reserve Amentioning
confidence: 96%
See 2 more Smart Citations
“…Based on these results and our earlier studies, 2,17,18 we propose in mouse ovary that small nuclear OCT-4 positive cells represent VSELs, while the slightly larger cytoplasmic OCT-4 positive cells represent OGSCs. To further confirm that VSELs are present in mouse ovary, flow cytometry experiment based on SCA-1þ/LinÀ/CD45À expression unique to VSELs 24 was carried out.…”
Section: Effect Of Chemotherapy On Mouse Ovarian Follicular Reserve Amentioning
confidence: 96%
“…More explanations for existing criticisms against the concept of ovarian stem cells and postnatal oogenesis were recently reviewed. 15,16 Our group has been working in the area of gonadal stem cells, and we have shown that they include 2 distinct populations, namely, the relatively ''quiescent'' very small embryonic-like stem cells (VSELs) and the more committed ''active'' progenitor stem cells, which include ovary germ stem cells (OGSCs) in ovary 2,17 and spermatogonial stem cells in testis. 18 The concept is very similar to the presence of quiescent and active stem cell population proposed in other organs like gut, skin, and bone marrow.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, others have also described the presence of stem cells in post-menopausal women OSE, which differentiate into oocytes and parthenote embryos in culture (Virant-Klun & Skutella 2010). Various events such as formation of germ cell nests, Balbiani body-like structures, and cytoplasmic streaming, which are extensively studied in fetal ovary, are recapitulated during in vitro oogenesis in adult OSE cultures along with characteristic expression of stem/ germ cell/oocyte markers (Parte et al 2014).…”
Section: R41mentioning
confidence: 99%
“…The authors in a separate study reported that they observed the formation of germ cell nests and Balbiani bodylike structures during fetal ovary development. 51 In another recent study by Sriraman et al, 52 VSELs were demonstrated to survive chemotherapy in mouse ovaries.…”
Section: Embryonic Stem Cells As a Potential Infertility Treatmentmentioning
confidence: 95%